The Potential Use of Osl Properties of Quartz in Investigating Fluvial Processes on the Catchment of River Mureş, Romania - Bartyik, Tamás; Floca, Cristian; Pál-Molnár, Elemér; Urdea, Petru; Hamed, Diaa Elsayed; Sipos, György (Journal of Environmental Geography, 2021)
To understand the functioning of fluvial systems it is important to investigate dynamics of sediment transport and the source of sediments. In case of reconstructing past processes these studies must be accompanied by the numerical dating of sediment samples. In this respect optically stimulated luminescence is a widely used technique, by which the time of sediment deposition can be directly dated. Recently, in various fluvial environments it has been shown that certain luminescence properties of minerals, and especially that of quartz, can be applied as indicators of fluvial erosion and/or sediment provenance. These properties are residual luminescence (or residual dose) and luminescence sensitivity of quartz grains. However, the values of the parameters above are affected by various factors, the importance of which is under debate. The present study therefore aims to assess these factors along a ~560 km long reach of River Mureş (Maros) a relatively large river with a compound surface lithology on its catchment. The research focused on the sandy fraction of modern sediments, collected from the main river and from three tributaries alike. This way not only longitudinal downstream changes, but the influence of tributaries could also be studied. Based on the data, both investigated parameters show a great variation, which can be attributed to the lithological differences of subcatchments and geomorphological drivers, such as erosional activity and potential number of sedimentary cycles, and human activity. However, relationships are not entirely clear and are influenced by the maximum grain size of the samples investigated, and the recycling of previously laid deposits with different properties. Still, when performing detailed dating studies, and tracing sediments from certain parts of the catchment luminescence properties can be a useful tool in the future.